Effect of tillage on the growth and yield of cowpea varieties in Sudan savanna agroecology of Northern Nigeria - Ewansiha, S.U.; Udensi, U.E.; Kamara, A. (Sciencedomain International, 2014)
Field study was conducted during the rainy seasons (July-November) of 2007, 2008, 2009 and 2010 at the Research Farm of the International Institute of Tropical Agriculture (IITA) Minjibir, Kano State, Nigeria; to compare responses of six cowpea varieties to tillage. The treatments consisted of tillage systems (zero tillage, flat tillage and ridge tillage) as the main plot and cowpea varieties (IT89KD-391, IT90K-277-2, IT97K-461-4, IT97K-499-35, IT98K-131-2, and IT98K-506-1) as the sub-plot. The treatments were arranged as split plot laid out in a randomized complete block design with four replications.